(untitled) (Dhaka University Journal of Biological Sciences, 2018)
Experiments were conducted for a period of 90 days to estimate the effects of different feeding frequencies (one time per day: T1, two times per day: T2, three times per day:T3 and four times per day: T4) on growth performance of gulsha fish reared in laboratory facilities. Significantly higher condition factor was observed in T2 (1.61 ± 0.02) and lowest in T4 (1.40 ± 0.01). Significantly lowest SGR and ADG were recorded in T4 fish fed four times per day. No significant difference was obtained among different treatments for FCR and survival rate. The highest RNA : DNA ratio (0.93 ± 0.07) was observed in fish of T2 and the lowest ratio (0.57 ± 0.11) was observed in fish of T1. The results of the present study suggest that in laboratory rearing two meals per day could be supplied for better growth performances as per indication of condition factor and RNA:DNA ratio. Dhaka Univ. J. Biol. Sci. 27(1): 75-83, 2018 (January)